2020
DOI: 10.1111/hir.12325
|View full text |Cite
|
Sign up to set email alerts
|

Finding useful cancer information may reduce cancer information overload for Internet users

Abstract: Background: An excessive overload of information causes an ineffective management of information, stress and indefiniteness. Furthermore, this situation can prevent persons from learning and making conscious decisions. Objective: This study aims to determine the cancer information overload (CIO) and the factors related to it in adults who are Internet users. Methods: A cross-sectional study with 482 Internet users was conducted. The data were collected by using an Introductory Information Form and the Cancer I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…It suggested that the IEx received influences the IO perceived by international students in Indonesia. This finding agrees with that of other research that the frequency of IEx is positively correlated with IO (Serçekuş et al, 2020;Soroya et al, 2021). It is related to the conditions of information production and distribution at the global level, which is characterized by the proliferation of media that present similar information with diverse styles and perspectives.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It suggested that the IEx received influences the IO perceived by international students in Indonesia. This finding agrees with that of other research that the frequency of IEx is positively correlated with IO (Serçekuş et al, 2020;Soroya et al, 2021). It is related to the conditions of information production and distribution at the global level, which is characterized by the proliferation of media that present similar information with diverse styles and perspectives.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in the distribution channels for the same information can lead to IO (Edmunds & Morris, 2000;Soroya et al, 2021). Other research reports that the frequency of IEx positively correlates with IO (Serçekuş et al, 2020;Soroya et al, 2021). Therefore, we propose the first hypothesis as follows:…”
Section: Information Exposurementioning
confidence: 89%
“…Similarly, Serçekuş, Gencer, and Özkan (2020) reported that the frequency of information source exposure is positively correlated with cancer information overload. Farooq et al.…”
Section: Theoretical Foundationmentioning
confidence: 96%
“…Consequently, solutions have been put forward to reduce the risk of overload (e.g. Serçekus ¸et al, 2020).…”
Section: Introductionmentioning
confidence: 99%